Analisis Perilaku Pada Mahasiswa Ekonomi Syariah Terhadap Belanja Online - Fufut Fitriy; Anya Regista Cahyani; Salsabilah Nurhidayah; Hadi Peristiwo; Wahyu Hidayat; Fitri Fitri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the behavior of Sharia Economics students towards online shopping. Online shopping has become an increasingly popular phenomenon among students, including Sharia Economics students, because of the convenience and ease it offers. Data for this study, which employs quantitative research methodologies, was gathered by distributing questionnaires to forty Sharia Economics students at Sultan Maulana Hasanuddin State Islamic University Banten's Faculty of Economics and Islamic Business. The results showed that factors such as ease of access, attractive offers, and various payment methods, including sharia methods, had a significant effect on students' online shopping behavior. In this study, the t table obtained a table number of 4.966 From the data above the sig value. 0.05 < X value (5.520), which means that the behavior analysis variable (X) has a significant effect on the online shopping variable (Y). It can be concluded that there is a significant relationship between the behavior analysis variable (X) and online shopping (Y) with a correlation value (R) of 0.667 This indicates a positive relationship between behavior analysis and online shopping. In addition, the coefficient of determination (R Square) of 0.445 indicates that about 44.5% of the variation in behavior analysis in Islamic economics students on online shopping. Keywords: Online Shopping, Behavior Analysis, Sharia Economics